Preparation and application of non-metallic element doped self-supporting cobalt oxide catalyst

CN122879746APending Publication Date: 2026-10-09NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610709699.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这种方法一方面是制备流程复杂、耗时较长且存在原材料大量浪费的问题,另一方面,这种水热处理生长的催化剂与基底结合不牢易脱落,导致稳定性不佳

Benefits of technology

[0027](1)本发明提供的非金属元素(硒)掺杂四氧化三钴纳米颗粒自支撑电催化剂,通过硒元素的掺杂有效调控了四氧化三钴的电子结构,优化了对氧基物种的吸附/脱附能力,降低了OER反应的能垒。实验结果表明,本发明制备的自支撑催化剂在0.5mol/L H2SO4溶液中,于10mA/cm2电流密度下,析氧过电位仅为289mV(vs.RHE),且在10mA/cm2恒电流密度下连续运行200小时,电位仅上升90mV,展现出极佳的催化活性和耐久性,优于大多数已报道的非贵金属酸性OER催化剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879746A_ABST
    Figure CN122879746A_ABST
Patent Text Reader

Abstract

The application specifically relates to a preparation method and application of a non-metal element doped tricobalt tetraoxide nanoparticle self-supporting electrocatalyst, and belongs to the technical field of electrocatalysis. The application obtains a precursor dispersion liquid by mixing a cobalt source, a non-metal element selenium source and a solvent and performing ultrasonic crushing treatment, uniformly deposits the precursor dispersion liquid on the surface of a conductive substrate by using a substrate assisted reactive spray deposition method, and finally performs annealing treatment in air to prepare a low-cost, large-scale producible selenium doped tricobalt tetraoxide self-supporting electrocatalyst for a proton exchange membrane water electrolysis oxygen evolution reaction. Experimental results show that the self-supporting electrocatalyst prepared by the application has an oxygen evolution overpotential of only 289 mV (vs. RHE) in a 0.5 mol / L H2SO4 solution at a current density of 10 mA / cm 2 2, and only a potential rise of 90 mV after continuous operation for 200 hours at a constant current density, thus exhibiting excellent catalytic activity and durability. 2 ​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalysis technology, specifically relating to a non-metallic element-doped cobalt tetroxide self-supporting electrocatalyst, its preparation method, and its application in the oxygen evolution reaction (OER) of acidic water electrolysis. Background Technology

[0002] With the continuous rise in global energy demand and the increasing depletion of traditional energy sources, human society is facing a critical challenge—how to build a sustainable energy system. Hydrogen energy, with its significant advantages such as high energy density and zero emissions at end-use, provides an important pathway for achieving large-scale clean energy applications. Among various hydrogen production technologies, water electrolysis technology has attracted considerable attention in recent years due to its clean process, compact system, and flexible operation, compared to methods such as photocatalytic decomposition, natural gas reforming, and biomass gasification. Particularly noteworthy is the proton exchange membrane electrolyzer (PEMWE), which exhibits outstanding technological competitiveness due to its high hydrogen purity and adaptability to high current density operation. However, in strongly acidic environments, the anode OER involves a four-electron transfer process, which is kineticly slow, limiting overall energy efficiency improvement. It is necessary to address the key bottlenecks of current PEMWE, such as slow OER kinetics in strongly acidic environments and high dependence on precious metal catalysts. Meanwhile, the localized high acidity environment created by the perfluorosulfonic acid proton exchange membrane (PFAS) places more stringent demands on the corrosion resistance and structural stability of the anode catalyst in the electrolyzer. The global carbon neutrality target requires increasing the share of green hydrogen in final energy sources to 12%-15% by 2050, while current water electrolysis for hydrogen production accounts for only about 4% of global hydrogen production, making technological iteration imperative. Domestic PEMWE still relies on imports for core components such as catalysts and membrane materials, with an annual demand gap of 30%-50% for iridium-based catalysts, posing a risk. Currently, the cost of green hydrogen (approximately US$3.5-5 / kg) is significantly higher than that of gray hydrogen (US$1.5-2 / kg), with investment in the electrolysis system accounting for over 50%, making catalytic efficiency and lifespan key levers for cost reduction. Therefore, developing acidic OER catalysts with both high activity and high stability has become a core issue that urgently needs to be addressed to promote the large-scale application of proton exchange membrane water electrolysis technology.

[0003] Related studies have found that using p-orbital atom doping (N, P, S, Se) can precisely control the electronic structure of RuO2, especially the electron configuration of Ru. g The energy gap between the orbital and the p orbital of O facilitates the transfer of electrons from the unbonded Op band to the Ru-e orbital. g Orbital transfer. At the OER potential, these electrons can move more rapidly from the ee orbital. gOrbital diffusion extends to the external circuit. This significantly accelerates the kinetics of the lattice oxygen-mediated process, thereby enhancing the initial activity of the OER. Inspired by this, the low electronegativity of Se may also effectively modulate the electronic structure of Co sites in Co3O4. In undoped Co3O4, oxygen has high electronegativity, and the bonding electron pairs are strongly biased towards oxygen atoms, resulting in a low electron density of Co. After Se doping, since Se's electronegativity is lower than O but still higher than Co's, the degree to which bonding electrons are biased towards Se is less than that towards O. The local electron density of Co atoms adjacent to Se is higher than that of Co atoms adjacent to O, making Co... 3+ To Co 4+ The conversion is more likely to occur, which improves the OER activity of the catalyst.

[0004] In existing technologies, some catalyst preparation methods disclose the use of a hydrothermal method, in which the catalyst is grown on a conductive substrate in a reaction vessel and then calcined. This method has several drawbacks: firstly, the preparation process is complex, time-consuming, and results in significant waste of raw materials; secondly, the catalyst grown by this hydrothermal treatment does not bond firmly to the substrate and is prone to detachment, leading to poor stability. Summary of the Invention

[0005] To address the aforementioned problems of existing non-precious metal-based catalysts, this invention aims to provide a method for preparing and applying a non-metallic element-doped cobalt tetroxide self-supported electrocatalyst, offering a novel design approach for non-precious metal-based supported catalyst materials. Specifically, by introducing the non-metallic element selenium into cobalt tetroxide, its electron feedback is utilized to regulate the electron transfer capability of cobalt tetroxide, thereby improving its electrochemical performance and achieving economical, efficient, and sustainable development of proton exchange membrane water electrolysis. This catalyst material preparation method is simple, low-cost, and suitable for large-scale production, possessing potential for industrial applications.

[0006] To achieve the above objectives, the specific technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a non-metallic element-doped cobalt tetroxide self-supporting electrocatalyst, characterized in that the non-metallic element-doped cobalt tetroxide nanoparticles are loaded onto a pretreated conductive substrate by ultrasonic-assisted deposition combined with annealing treatment.

[0008] As one embodiment of the present invention, the ultrasonic-assisted deposition method includes: mixing a cobalt source, a non-metallic source, and a solvent, followed by ultrasonic disruption to obtain a precursor colloidal dispersion; depositing the precursor colloidal dispersion onto the surface of a pretreated conductive substrate, drying it, and repeating the deposition to obtain a conductive substrate loaded with the precursor; and annealing the conductive substrate loaded with the precursor to obtain a self-supporting electrocatalyst of cobalt tetroxide nanoparticles doped with non-metallic elements.

[0009] In one embodiment of the present invention, the non-metallic source is a selenium source; the selenium source is at least one selected from sodium selenite, selenium dioxide, selenium powder, or sodium selenosulfate. Preferably, in some specific embodiments, the selenium source is sodium selenite (Na2SeO3).

[0010] In one embodiment of the present invention, the cobalt source is a cobalt salt; the cobalt salt is at least one selected from cobalt nitrate, cobalt acetylacetonate, cobalt acetate, and cobalt carbonate. Preferably, in some specific embodiments, the cobalt source is cobalt nitrate (Co(NO3)2·6H2O).

[0011] In one embodiment of the present invention, the solvent is a mixture of water and alcohol; the alcohol is at least one selected from ethanol, isopropanol, or methanol. In some specific embodiments, the alcohol is ethanol. The present invention has found that adding an appropriate amount of ethanol to the solvent can significantly improve the dispersibility of the precursor colloidal dispersion and the uniformity of its loading on the conductive substrate, and that the volume ratio of ethanol to water has a certain influence on the performance of the final catalyst.

[0012] In one embodiment of the present invention, the volume ratio of water to alcohol is 1:0.5 to 3. Preferably, in some specific embodiments, the volume ratio of water to alcohol is 1:2.

[0013] In one embodiment of the present invention, the molar ratio of cobalt source to non-metallic source in the precursor colloidal dispersion is 1:0.05 to 0.2. Preferably, in some specific embodiments, the molar ratio of cobalt source to selenium source is 1:0.05, 1:0.1, 1:0.15, or 1:0.2.

[0014] In one embodiment of the present invention, the ultrasonic disruption treatment time is 5 to 20 minutes, for example, 5 minutes, 10 minutes, 15 minutes, or 20 minutes. In some specific embodiments, the ultrasonic disruption treatment time is 10 minutes. It is worth noting that when a selenium source (such as sodium selenite) is added to a cobalt source aqueous solution, a precipitate is immediately formed, but after ultrasonic disruption treatment, a uniform and stable colloidal dispersion can be formed. This is one of the key technical features of the present invention for achieving uniform loading.

[0015] As one embodiment of the present invention, the deposition method is one of drip coating, spray coating, or spin coating. Preferably, in some specific embodiments, spray coating is used.

[0016] As one embodiment of the present invention, the single deposition volume is 10–50 μL / cm³. 2 The deposition process is repeated 2 to 10 times. Preferably, in some specific embodiments, for 1×2cm... 2The conductive substrate was coated with 20 μL in a single drop, and the coating was repeated 5 times, with a total deposition volume of 100 μL.

[0017] In one embodiment of the present invention, drying after each deposition is performed by heating or infrared drying; the drying temperature is 50–100°C, for example, 40°C, 50°C, 60°C, 70°C, or 80°C. Preferably, in some specific embodiments, infrared drying is used for rapid drying.

[0018] In one embodiment of the present invention, the annealing process is carried out in an air atmosphere at a temperature of 300–400°C and a holding time of 1–3 hours. Preferably, in some specific embodiments, the annealing temperature is 350°C and the holding time is 2 hours.

[0019] In one embodiment of the present invention, the heating rate of the annealing treatment is 1 to 5 °C / min, for example, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min or 5 °C / min. Preferably, in some specific embodiments, the heating rate is 5 °C / min.

[0020] In one embodiment of the present invention, the conductive substrate is one of platinum-plated titanium felt, carbon paper, carbon cloth, titanium felt, or fluorine-doped tin oxide. Preferably, in some specific embodiments, the conductive substrate is platinum-plated titanium felt.

[0021] As one embodiment of the present invention, the pretreatment includes ultrasonically cleaning the conductive substrate sequentially with anhydrous ethanol, isopropanol, and water, followed by drying. Preferably, in some specific embodiments, the ultrasonic cleaning time is 5–30 minutes to remove residual stains on the surface, followed by drying in a 70°C oven overnight.

[0022] As one embodiment of the present invention, and for comparison, an undoped cobalt tetroxide self-supporting electrocatalyst was prepared using the same method without adding a non-metallic source.

[0023] Secondly, the present invention also provides the application of the above-mentioned non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst in acidic OER reaction.

[0024] As one embodiment of the present invention, the application of the non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst in acidic OER reaction includes the following steps: using the self-supporting electrocatalyst prepared above as the working electrode, using a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode to construct a three-electrode system, and performing electrocatalytic OER reaction testing in an acidic solution.

[0025] As one embodiment of the present invention, the acidic solution is an H2SO4 solution with a concentration of 0.05 to 1.0 mol / L, preferably 0.5 mol / L.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The non-metallic element (selenium)-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst provided by this invention effectively regulates the electronic structure of cobalt tetroxide through selenium doping, optimizes the adsorption / desorption capacity for oxygen species, and lowers the energy barrier of the OER reaction. Experimental results show that the self-supporting catalyst prepared by this invention exhibits good performance in 0.5 mol / L H2SO4 solution at 10 mA / cm². 2 At the current density, the oxygen evolution overpotential is only 289 mV (vs. RHE), and at 10 mA / cm², the overpotential is only 289 mV (vs. RHE). 2 After 200 hours of continuous operation at constant current density, the potential only increased by 90mV, demonstrating excellent catalytic activity and durability, which is superior to most reported non-precious metal acidic OER catalysts.

[0028] (2) This invention employs an ultrasonic-assisted spray deposition method combined with annealing. Short-duration ultrasonic disruption using an ultrasonic disruptor transforms the precipitate generated in the reaction into a homogeneous colloid within the system. The introduction of ethanol into the solvent significantly improves the dispersibility and loading uniformity of the catalyst precursor, avoiding the need for complex precursor solution preparation and related electrodeposition equipment. This method is simple to operate, operates under mild conditions, and has good repeatability. It eliminates the need for binders, enhances the bonding force between the catalyst and the conductive substrate, and simultaneously ensures high loading capacity and excellent electron transport performance.

[0029] (3) The preparation method of the present invention can flexibly control the composition, morphology and catalytic performance of the catalyst by adjusting parameters such as the molar ratio of cobalt source to non-metallic source, the volume ratio of water to alcohol in the solvent, the number of spray depositions and the annealing temperature. The entire synthesis process does not involve toxic or expensive reagents, has low energy consumption (low temperature annealing), and is suitable for large-scale production and practical applications. Attached Figure Description

[0030] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0031] Figure 1 This is a SEM image of the material from Example 1.

[0032] Figure 2 The images show the XRD patterns of the Se-Co3O4 prepared in Example 1 and the Co3O4 material prepared in Comparative Example 1.

[0033] Figure 3The linear sweep voltammetry curves for the materials in Examples 1, 2, 3, and Comparative Example 1 are shown. The test environment was a three-electrode system with a platinum wire as the counter electrode, Ag / AgCl as the reference electrode, and 0.5 mol / L H2SO4 as the electrolyte solution.

[0034] Figure 4 The linear sweep voltammetry curves for the materials in Example 1, Comparative Example 1, and Comparative Example 2 are shown. The test environment was a three-electrode system with a platinum wire as the counter electrode, Ag / AgCl as the reference electrode, and 0.5 mol / L H2SO4 as the electrolyte solution.

[0035] Figure 5 The materials used in Example 1, Comparative Example 1, and Comparative Example 2 were at 10 mA / cm 2 The constant current curve at the current density was obtained. The test environment was a three-electrode system with a platinum wire as the counter electrode, Ag / AgCl as the reference electrode, and the electrolyte solution was 0.5 mol / L H2SO4. Detailed Implementation

[0036] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the embodiments will be systematically described below with reference to the accompanying drawings. It should be understood that the illustrated embodiments are merely some specific examples of this invention and not limitations on the scope of protection. All other embodiments that can be obtained by those skilled in the art based on these embodiments without creative effort should be considered to fall within the scope of protection of this invention.

[0037] Example 1

[0038] This example demonstrates the preparation of a 10% Se-Co3O4 catalyst.

[0039] (1) Select a platinum-plated titanium felt with a platinum layer thickness of 0.5μm and cut it into 1*2cm. Place the substrate in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning for 20min each to remove surface stains. Then place it in a 70℃ oven to dry overnight.

[0040] (2) Transfer 250 μL of pure water into a microcentrifuge tube using a pipette, weigh 291 mg of cobalt nitrate hexahydrate (1 mmol) and add it to the centrifuge tube. After sonicating until completely dissolved, add 500 μL of ethanol to assist dispersion, and sonicate again until the solution is completely homogeneous. Then add 17.3 mg of sodium selenite (0.1 mmol). A purple precipitate will appear immediately. Immediately use an ultrasonic disruptor to process it, and use an ice-water bath to assist in heat dissipation to avoid excessive local temperature. The ultrasonic disruptor should work for five seconds and then stop for five seconds, continuing for ten minutes to avoid overheating of the instrument and to ensure complete dispersion of the obtained precursor.

[0041] (3) Take the platinum-plated titanium felt prepared in step (1), use a pipette to transfer 20 μL of the precursor prepared in (2) into the spray gun, use the spray gun to evenly spray the precursor onto the platinum-plated titanium felt, and then place it under an infrared heating lamp to dry. After drying, repeat the operation five times in total, and transfer a total of 100 μL of precursor to the 1*1 cm position on the surface of the platinum-plated titanium felt. After it is basically dry, transfer it to a 60℃ vacuum drying oven to dry overnight.

[0042] (4) The catalyst precursor in step (3) is placed in a muffle furnace for annealing. The temperature is increased to 350°C at a heating rate of 5°C / min and held for 2 hours. After natural cooling with the furnace, 10% Se-Co3O4 catalyst is obtained. The catalyst is ultrasonicated in pure water for 10 seconds to remove loosely adhered particles, and then dried.

[0043] Example 2

[0044] This example demonstrates the preparation of a 5% Se-Co3O4 catalyst.

[0045] The difference between this embodiment and Example 1 is that the amount of sodium selenite added is reduced from 17.3 mg to 8.65 mg.

[0046] Example 3

[0047] This example demonstrates the preparation of a 20% Se-Co3O4 catalyst.

[0048] The difference between this embodiment and Example 1 is that the amount of sodium selenite added is increased from 17.3 mg to 34.6 mg.

[0049] Comparative Example 1

[0050] This comparative example illustrates the preparation of a Co3O4 catalyst.

[0051] The difference between this comparative example and Example 1 is that it is not doped with Se.

[0052] Comparative Example 2

[0053] This comparative example describes the preparation of the same molar amount of Se powder-Co3O4 catalyst as in Example 1.

[0054] (1) Select a platinum-plated titanium felt with a platinum layer thickness of 0.5μm and cut it into 1*2cm. Place the substrate in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning for 20min each to remove surface stains. Then place it in a 70℃ oven to dry overnight.

[0055] (2) Take a microcentrifuge tube as a container, transfer 250 μL of pure water into it with a pipette, weigh 291 mg of cobalt nitrate hexahydrate (1 mmol) into the centrifuge tube, sonicate until completely dissolved, add 500 μL of ethanol to assist dispersion, then add 20 μL of 5% perfluorinated resin solution with a pipette, sonicate again until the solution is completely homogeneous, then add 7.9 mg of Se powder (0.1 mmol), immediately process with an ultrasonic disruptor, use an ice water bath to assist heat dissipation to avoid local overheating, and the ultrasonic disruptor needs to work for five seconds and then stop for five seconds, continue for ten minutes to avoid overheating of the instrument and ensure complete dispersion of the obtained precursor;

[0056] (3) Take the platinum-plated titanium felt prepared in step (1), use a pipette to transfer 20 μL of the precursor prepared in (2) into the spray gun, use the spray gun to evenly spray the precursor onto the platinum-plated titanium felt, and then place it under an infrared heating lamp to dry. After drying, repeat the operation five times in total, and transfer a total of 100 μL of precursor to the 1*1 cm position on the surface of the platinum-plated titanium felt. After it is basically dry, transfer it to a 60℃ vacuum drying oven to dry overnight.

[0057] (4) The catalyst precursor in step (3) is placed in a muffle furnace for annealing. The temperature is increased to 350°C at a heating rate of 5°C / min and held for 2 hours. After natural cooling in the furnace, a 10% Se-Co3O4 catalyst is obtained. The catalyst is ultrasonicated in pure water for 10 seconds to remove loosely adhered particles, and then dried to obtain the catalyst.

[0058] Performance testing

[0059] (1) SEM (Scanning Electron Microscopy) analysis

[0060] The 10% Se-Co3O4 prepared in Example 1 was analyzed by SEM scanning electron microscopy, and the results are shown in Figure 1.

[0061] from Figure 1 It can be seen that the catalyst prepared by the present invention consists of uniformly sized nanoparticles with a particle size of about 50 nm, which are densely arranged on a platinum-plated titanium felt substrate.

[0062] (2) XRD analysis

[0063] XRD analysis was performed on catalyst samples from Example 1, Comparative Example 1, and Comparative Example 2. The results are as follows: Figure 2 As shown.

[0064] from Figure 2As can be seen, in Example 1, the crystal structure did not change significantly after the introduction of Se compared to Comparative Example 1; only the diffraction peak intensity decreased, and there were no impurity peaks, indicating that Se was successfully doped into the Co3O4 lattice. In Comparative Example 2, the XRD changes were similar to those in Comparative Example 1 after the introduction of Se, indicating that the introduction of Se did not cause a significant change in the crystal structure of Co3O4.

[0065] (3) OER test

[0066] The catalysts from Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 were subjected to OER testing, and the results are as follows: Figure 3 , Figure 4 As shown.

[0067] Figure 3 LSV curves of Se-Co3O4 with different doping ratios, from Figure 3 It can be seen that the catalyst with a 10% doping ratio in Example 1 exhibits the best performance at 10 mA / cm². 2 The overpotential at the given current density is 289 mV, indicating that the catalyst prepared in this invention has good performance.

[0068] Figure 4 LSV curves of catalysts prepared for different selenium sources, from Figure 4 It can be seen that the catalytic activity of sodium selenite as the selenium source in Example 1 is significantly improved compared with that of selenium powder in Comparative Example 2, indicating that the catalyst prepared by the present invention has good performance.

[0069] (4) Stability test

[0070] The catalysts of Example 1, Comparative Example 1, and Comparative Example 2 were subjected to stability tests, and the results are as follows: Figure 5 As shown.

[0071] from Figure 5 It can be seen that the catalyst prepared in Example 1 of this invention has a performance of 10 mA / cm². 2 At the specified current density, after a long-term durability test of 200 hours, the potential increased by about 90 mV, indicating that Example 1 has good stability and has a better advantage among published non-precious metal-based catalysts.

[0072] In summary, this invention prepares a non-precious metal electrocatalyst for PEM water electrolysis by ultrasonically breaking down cobalt and selenium sources in an alcohol-water mixed solvent to form a homogeneous colloid. The precursor is then loaded onto a pretreated conductive substrate using an ultrasonic-assisted deposition method. Controllable loading is achieved through multiple spray-drying processes, followed by low-temperature annealing in air. Experimental results show that the self-supporting non-precious metal electrocatalyst prepared in this invention exhibits excellent catalytic activity and long-term stability under acidic conditions, with an OER overpotential of only 289 mV at a current density of 10 mA / cm², and a potential rise of only 90 mV after 200 hours of continuous operation. Compared to precious metal iridium-ruthenium catalysts, the non-precious metal elements such as cobalt and selenium used in this invention are inexpensive and abundant, providing important guidance for reducing the cost of industrial-scale PEM water electrolysis catalysts.

[0073] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A self-supporting electrocatalyst doped with non-metallic elements, specifically cobalt tetroxide nanoparticles, characterized in that... The non-metallic element-doped cobalt tetroxide nanoparticles are loaded onto a pretreated conductive substrate by ultrasonic-assisted spray deposition combined with annealing, including the following steps.

2. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 1, characterized in that, The ultrasonic-assisted spray deposition method includes the following steps; S1. After mixing and dissolving the cobalt source and selenium source in the corresponding solvent, ultrasonically break them down to obtain a cobalt selenium precursor dispersion. S2. Deposit the precursor colloidal dispersion onto the surface of a pretreated conductive substrate and then dry it. S3. Repeat step S2 to obtain a conductive substrate loaded with the precursor. S4. The conductive substrate loaded with the precursor in step S3 is calcined to obtain the desired product.

3. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 1, characterized in that, The conductive substrate is one of platinum-plated titanium felt, carbon paper, carbon cloth, titanium felt, or fluorine-doped tin oxide.

4. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 1, characterized in that, The pretreatment includes ultrasonically cleaning the conductive substrate sequentially with anhydrous ethanol, isopropanol, and water, followed by drying.

5. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S1, the non-metallic source is a selenium source; the selenium source is at least one of sodium selenite, selenium dioxide, selenium powder, or sodium selenosulfate.

6. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S1, the solvent is a mixture of water and alcohol; the alcohol is at least one of ethanol, isopropanol, or methanol; and the volume ratio of water to alcohol is 1:0.5 to 3.

7. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S1, the molar ratio of cobalt source to non-metallic source in the precursor colloidal dispersion is 1:0.05 to 0.2; the ultrasonic disruption treatment time is 5 to 20 minutes.

8. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S2, the deposition method is one of drop coating, spray coating, or spin coating; the single deposition volume is 10–50 μL / cm³. 2 The deposition occurs 2 to 10 times.

9. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S2, the drying is performed by heating or infrared drying; the drying temperature after each deposition is 40–80°C.

10. The non-metallic element-doped cobalt tetroxide nanoparticle self-supporting electrocatalyst according to claim 2, characterized in that, In step S4, the annealing process is carried out in an air atmosphere, the annealing temperature is 300-400℃, and the holding time is 1-3h; the heating rate of the annealing process is 1-5℃ / min.